Kesintasan Hidup Satu Tahun Pasien Sirosis Hati yang Dirawat di Rumah Sakit Cipto Mangunkusumo pada Periode COVID-19 - Aprilicia, Gita; Baihaki, Ichwan; Banjarnahor, Riri Oktavani; Kalista, Kemal Fariz; Gani, Rino Alvani (Jurnal Penyakit Dalam Indonesia, 2026)
Introduction. Liver cirrhosis represents the terminal stage of chronic liver disease and is characterized by a markedly reduced survival rate. Understanding the characteristics and laboratory parameters of patients with liver cirrhosis can provide valuable insights into their prognosis and potential interventions. This study was conducted during the COVID-19 pandemic period, which may have influenced patient outcomes due to potential impact of COVID-19 infection on patients with chronic liver disease. This study aimed to evaluate the one-year survival rate of hospitalized liver cirrhosis patients at Cipto Mangunkusumo Hospital during the COVID-19 and to identify clinical and laboratory factors associated with patient survival. Methods. This retrospective study analyzed data from 73 in-hospital liver cirrhosis patients during January to December 2020. Demographic characteristics, comorbidities, diagnosis upon admission, and laboratory parameters were collected. Patients were categorized into two groups: those who survived and those who died within one year of hospitalization. Survival analysis was performed using the Kaplan–Meier method to estimate 1 year survival probability of cirrhosis patients. Results. The analysis revealed significant differences in several characteristics and laboratory parameters between the survival and death groups during COVID-19 period. The etiology of liver cirrhosis was predominantly related to HBV (41.1%) and HCV (23.3%), which constituted the most common causes. Diagnosis upon admission showed a significant association with survival, with bleeding esophageal varices (53.4%) being the most prevalent. Laboratory parameters such as SGOT, SGPT, albumin, bilirubin, prothrombin time, INR, and Child Pugh score demonstrated significant differences between the two groups. The 1-year survival rate for the Child Pugh class A, B and C was approximately 100%, 61.2% (CI 95% 42.2 - 80.2%) and 0%, respectively. The overall 1-year survival rate of in-hospital liver cirrhosis patients was 52.6% (CI 95% 38.7 - 66.5%). Conclusions. This study found the overall survival of in-hospital liver cirrhosis patients during COVID-19 period was low. It’s essential to develop a comprehensive and personalized treatment plan for optimal patient outcomes.